Hard times : economic depressions in America - Striner, Richard, 1950- (American ways series., 2018)
Hard Times presents a comprehensive account of economic depressions in America, from colonial times to the "great recession" that began in 2008. Striner conveys how Americans have always endured and rebounded from hard times, emerging as a stronger nation in the aftermath of each downturn.